Light Regulates Transcription of Chlorophyll Biosynthetic Genes During Chloroplast Biogenesis. (2nd January 2017) - Yuan, Ming; Zhao, Yu-Qing; Zhang, Zhong-Wei; Chen, Yang-Er; Ding, Chun-Bang; Yuan, Shu
ABSTRACT: Chlorophyll (Chl) biosynthesis requires highly efficient metabolic regulation during chloroplast biogenesis in angiosperms. The intermediates of Chl biosynthesis and Chls are easily activated by light and simultaneously interact with oxygen, resulting in highly toxic levels of reactive oxygen species. A stable supply and correct stoichiometry of Chl is essential to photosynthesis and plant development. Light is an indispensable environmental cue for Chl biosynthesis in angiosperms and regulates the transcription of light-mediated genes and histone modifications. Here, we reviewed the transcriptional regulation of chlorophyll biosynthesis-related genes by light and the coordinated relationship network of the expression of these genes. Nuclear-encoded genes involved in Chl biosynthesis and photosynthesis and chloroplast-encoded photosynthetic genes are expressed cooperatively to effectively assemble photosystems during de-etiolation. The expression of POR genes may be a key mechanism for light regulation of Chl biosynthesis. HY5, RVE1, CCA1, EIN3, DELLA, GLK, and PIF1 might be involved in the light regulation of POR expression. Plastid-light signals induce multiple histone acetylation and methylation modifications of promoters of Chl biosynthesis-related genes (including H3K4, 9, 27, 36me3, H3K9me2, and H3K9, 14, 27ac) or promoters of key Chl biosynthesis-related transcription factor genes (such as HY5 and ABI4 ).